Guide for diagnosis and treatment of hyperphenylalaninemia. Issue 1 (10th January 2021) - Shintaku, Haruo; Ohura, Toshihiro; Takayanagi, Masaki; Kure, Shigeo; Owada, Misao; Matsubara, Yoichi; Yoshino, Makoto; Okano, Yoshiyuki; Ito, Tetsuya; Okuyama, Torayuki; Nakamura, Kimitoshi; Matuo, Masafumi; et al.
Abstract: Importance: Sapropterin hydrochloride, a natural coenzyme (6R‐tetrahydrobiopterin) of phenylalanine hydroxylase, was first approved as a treatment for tetrahydrobiopterin deficiency in 1992 in Japan, and was then approved as a treatment for a tetrahydrobiopterin‐responsive hyperphenylalaninemia in 2007 and 2008, in the USA and Japan, respectively. Guidelines are required on the proper use of sapropterin hydrochloride for tetrahydrobiopterin‐responsive hyperphenylalaninemia. Observations: It is recommended that tetrahydrobiopterin‐responsive hyperphenylalaninemia should be diagnosed in all cases of hyperphenylalaninemia, including phenylketonuria, by tetrahydrobiopterin administration tests rather than by phenotype or blood phenylalanine levels. Conclusions and Relevance: If tetrahydrobiopterin‐responsive hyperphenylalaninemia is diagnosed, all ages can be treated with sapropterin hydrochloride. Although there are reports that sapropterin hydrochloride is effective and safe for the prevention of maternal phenylketonuria, further investigation is required.